2023
DOI: 10.1001/jamanetworkopen.2023.35511
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Age of Nonalcoholic Fatty Liver Disease and Cancer Risk

Chenan Liu,
Tong Liu,
Qingsong Zhang
et al.

Abstract: ImportanceThe onset age of nonalcoholic fatty liver disease (NAFLD) is decreasing, and whether earlier ages of NAFLD onset are associated with increased cancer risk is currently unclear.ObjectiveTo explore the association between NAFLD new-onset age and cancer risk.Design, Setting, and ParticipantsThis cohort study was conducted among 179 328 participants included in the Kailuan Cohort Study between 2006 and 2021. In total, 46 100 incident NAFLD cases were identified. For each case, a participant matched by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The largest proportion of people were aged 40-59 years in our study. A cohort study showed that risk factors, prevalence, and characteristics of NAFLD patients varied by age group ( 42 ). Consider this about the fact that senescent cells cause age-related tissue degeneration and that the accumulation of senescent cells promotes hepatic fat accumulation and steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…The largest proportion of people were aged 40-59 years in our study. A cohort study showed that risk factors, prevalence, and characteristics of NAFLD patients varied by age group ( 42 ). Consider this about the fact that senescent cells cause age-related tissue degeneration and that the accumulation of senescent cells promotes hepatic fat accumulation and steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, studies using the same Scandinavian public health data resources as those used in this study have quantified a significant disease burden in this younger age group that is associated with an increased long-term mortality risk 8 . A recently published prospective cohort study of 35,860 Chinese patients also suggested that an earlier onset of MASLD was linked with a higher risk of liver cancer with an adjusted HR of 2.66 for those under the age of 45 9 . The exclusion of this patient group from the analysis has the potential to affect both the primary and secondary outcome measures and the conclusions drawn therein.‬…”
mentioning
confidence: 86%
“…This involved using the significance levels of the cubic, quadratic, and linear terms to determine the most appropriate functional form for each trajectory pattern. 10,13,14 Inflammation and MetS may interact in a synergistic manner to increase the risk of cancer. 15 To further investigate this association, we conducted a subgroup analysis by categorizing participants based on their CRP levels.…”
Section: Statistical Analysesmentioning
confidence: 99%